2023
DOI: 10.1002/oby.23639
|View full text |Cite
|
Sign up to set email alerts
|

Obesity among Asian American people in the United States: A review

Abstract: Standard measures of obesity, i.e., body weight and BMI, suggest that Asian American people have a lower obesity prevalence than other racial groups in the United States. However, Asian American people face a unique challenge in their pattern of adiposity with central obesity, which raises the risk for multiple comorbidities, such as type 2 diabetes, metabolic syndrome, and cardiovascular disease, at a lower BMI compared with other populations. Several organizations recommend lower BMI cutoffs for obesity in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…One population is patients who have serious concerns about weight gain and want to keep their body shape, especially models and women. Another population is patients with pre-existing obesity-related diseases, such as chronic obstructive pulmonary disease, arthritis, cardiovascular disease, and metabolism disease; the BMI increase could result in severe functional disability in these patients with pre-existing diseases [ 35 , 36 ]. Given the anxiety and deterioration of pre-existing diseases caused by weight gain, specific patients would prefer EETS for its advantage in weight control.…”
Section: Discussionmentioning
confidence: 99%
“…One population is patients who have serious concerns about weight gain and want to keep their body shape, especially models and women. Another population is patients with pre-existing obesity-related diseases, such as chronic obstructive pulmonary disease, arthritis, cardiovascular disease, and metabolism disease; the BMI increase could result in severe functional disability in these patients with pre-existing diseases [ 35 , 36 ]. Given the anxiety and deterioration of pre-existing diseases caused by weight gain, specific patients would prefer EETS for its advantage in weight control.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to a lack of agreement among researchers, it did not establish distinct BMI cutoffs for this population. In recent years, further studies have led some groups to adopt different BMI and abdominal obesity thresholds for Asians and even for different Asian groups [73,74]. Research has shown that Asian individuals tend to accumulate weight around the central region of their bodies, and at a faster rate than other ethnic groups [75].…”
Section: Discussionmentioning
confidence: 99%
“…Both groups of users showed an equal gender distribution. Further, the group was assigned to the BMI categorization system based on the ASIAN standard [21,22]. Most laptop users (73.3%) were observed within normal weight ranges, whereas only 6.7% were underweight.…”
Section: Demographic Characteristicsmentioning
confidence: 99%